Awareness people about anemia and the scientific methods used to determine its type and combate it in all society classes - Mohammed Haji AlBriman; Ahmad Abdulla ALNahwi; Aqeel Jawad Abdullah ALMutlaq; Abdulhadi Nazar Alhaji; Maryam Abdullah Alsalman; Hawra Abdullah ALdrees; Salwa Ali Alrizq (International Journal of Medical Toxicology and Legal Medicine, 2024)
Anemia is a problem of not having sufficient and healthy red blood cells to carry oxygen from the lungs to all body tissues, or not sufficient hemoglobin concentration inside the red blood cells. anemia is a major public health concern affecting mainly children